2013
DOI: 10.1111/adj.12116
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary implant overdentures: current controversies

Abstract: Mandibular implant overdentures have established and predictable benefits over traditional mucosa-borne mandibular dentures and now form part of mainstream dentistry. Maxillary implant overdentures present a number of different challenges. This selective review highlights the paucity of evidence and inconsistent findings in the maxillary implant overdenture literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
0
24
0
5
Order By: Relevance
“…Literature reviews and systematic reviews with meta‐analyses do reveal conflicting evidence on surgical recommendations for maxillary implant overdentures when evaluating the quality of clinical trials and opposing mandibular prostheses/dentitions. Sadowsky suggested four implants with good bone quality, but six implants in compromised bone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature reviews and systematic reviews with meta‐analyses do reveal conflicting evidence on surgical recommendations for maxillary implant overdentures when evaluating the quality of clinical trials and opposing mandibular prostheses/dentitions. Sadowsky suggested four implants with good bone quality, but six implants in compromised bone.…”
Section: Introductionmentioning
confidence: 99%
“…This is in comparison with lower survival rate of 95.2%, when four implants are used with ball attachments. However, Dudley concluded that evidence for maxillary overdentures was still inconsistent, poorly standardized, and could not be cumulatively analyzed. Recommendations were for standardized research to provide more robust guidelines for maxillary implant overdenture management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent reviews on implants in the edentulous maxilla summarized data on FDP and IOD, presenting a larger number of patients with fixed prostheses as compared to IOD . IOD studies do not exhibit a common opinion with regard to the best anchorage and fixation system or the best prosthesis design and one study confirms that in the literature inconsistent findings for maxillary IOD are more frequent as compared to mandibular ones …”
Section: Discussionmentioning
confidence: 95%
“…Systematic reviews concluded that maxillary overdentures on 4 or more implants in a splinted construction provided high survival (> 95% for the first year) both for implants and overdenture 14,48. Long-term results regarding maxillary implant overdentures are still rare and when available often inconsistent 49. However, following the recommendation to use 4 or more implants splinted with a bar system a maxillary overdenture can be a successful treatment option (Fig.…”
Section: Maxilary Implant Overdenturementioning
confidence: 99%